The empirical study on market liquidity and determinants of Sukuk in Malaysia - Amirul Hamiza, Abd. Hamid (2017)
The purpose of this study is to examine the relationship between market liquidity and the determinants of sukuk in Malaysia's perspective. In this paper, sukuk's determinants are represented by variables; maturity, coupon rate, age, credit rating, number of trades and amount of trading. A sample of 933 issued sukuk in Malaysia is collected from secondary data of Bond Pricing of Agency Malaysia (BP AM) and Bond Info hub of Bank Negara Malaysia from period of 2005 to 2015. The sample of issued sukuk is based on Malaysian Ringgit denominated currency and these sukuk are actively traded in the secondary market of Malaysia. The sample is comprises five (5) sectors inclusive government, quasi-government, finance, Asset Backed Securities (ABS) and corporates. There are two (2) measurements of market liquidity used in this study which are the bid-ask spread and the amihud (2002) measure. The empirical results of this study show that age and maturity have positive relationship with sukuk market liquidity and they are significantly correlated. From the analysis, researcher concludes that investors prefer to hold their securities until meet its maturity rather than traded it in the secondary market as it makes the market to be illiquid.